2016
DOI: 10.18632/oncotarget.7839
|View full text |Cite
|
Sign up to set email alerts
|

Combining BRAF inhibitor and anti PD-L1 antibody dramatically improves tumor regression and anti tumor immunity in an immunocompetent murine model of anaplastic thyroid cancer

Abstract: The interaction of programmed cell death-1 and its ligand is widely studied in cancer. Monoclonal antibodies blocking these molecules have had great success but little is known about them in thyroid cancer. We investigated the role of PD-L1 in thyroid cancer with respect to BRAF mutation and MAP kinase pathway activity and the effect of anti PD-L1 antibody therapy on tumor regression and intra-tumoral immune response alone or in combination with BRAF inhibitor (BRAFi). BRAFV600E cells showed significantly high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 61 publications
5
77
1
Order By: Relevance
“…These results demonstrate that a strongly immunosuppressive molecular profile may be elicited in the tumor microenvironment of papillary thyroid carcinomas positive for the BRAF V600E mutation, suggesting that the promotion of tumor immune escape may be a mechanism by which the BRAF V600E mutation may contribute to aggressive tumor behavior (Angell et al 2014). Following this rationale, Brauner and coworkers thoroughly investigated the PD-1/PD-L1 immune checkpoint mechanism in a thyroid cancer model (Brauner et al 2016). In their study, the authors demonstrated that thyroid cell lines and tumor specimens with the BRAF V600E mutation displayed higher baseline expression of PD-L1 mRNA compared with BRAF WT thyroid cells and BRAF WT tumor samples, respectively.…”
Section: :12mentioning
confidence: 95%
“…These results demonstrate that a strongly immunosuppressive molecular profile may be elicited in the tumor microenvironment of papillary thyroid carcinomas positive for the BRAF V600E mutation, suggesting that the promotion of tumor immune escape may be a mechanism by which the BRAF V600E mutation may contribute to aggressive tumor behavior (Angell et al 2014). Following this rationale, Brauner and coworkers thoroughly investigated the PD-1/PD-L1 immune checkpoint mechanism in a thyroid cancer model (Brauner et al 2016). In their study, the authors demonstrated that thyroid cell lines and tumor specimens with the BRAF V600E mutation displayed higher baseline expression of PD-L1 mRNA compared with BRAF WT thyroid cells and BRAF WT tumor samples, respectively.…”
Section: :12mentioning
confidence: 95%
“…Moreover, the field of immunooncology has emerged in the past years and an interaction between somatic mutations and the tumor microenvironment has impressively been shown in several human malignancies (Danilova et al 2016). Whether combining targeted therapies and immune therapy in ATC patients as suggested for other advanced human malignancies and by in vivo data from preclinical thyroid cancer animal models is an effective approach which needs to be further elucidated (Brauner et al 2016).…”
Section: Targeted Therapymentioning
confidence: 99%
“…Recently, in case reports, efficacy of targeted therapy approaches has been reported. Moreover, checkpoint inhibitors might represent new treatment options (Brauner et al 2016, Latteyer et al 2016b.…”
Section: Introductionmentioning
confidence: 99%
“…In such mouse models, it is now possible to evaluate the efficacy of immune checkpoint inhibitors and combined therapies for treatment of aggressive thyroid cancer. This approach has recently been shown to result in dramatically improved tumor regression under combined BRAF inhibitor and PD-L1 antibody treatment (baseline: 782.3 ± 174.6 mm 3 vs 439.3 ± 188.4 mm 3 (BRAF inhibitor) and 716.7 ± 62.1 mm 3 (PD-L1) to 147.3 ± 60.8 mm 3 with BRAF inhibitor/PD-L1 combination) (Brauner et al 2016). In addition, a very recent study from Parhar et al demonstrated the influence of IL-12 on immune response and tumor growth in BRAF V600E mice.…”
Section: :10mentioning
confidence: 99%